TOLERANSI ANTAR UMAT BERAGAMA DALAM PERAYAAN LOVELY DESEMBER DI TANA TORAJA: TOLERANSI ANTAR UMAT BERAGAMA DALAM PERAYAAN LOVELY DESEMBER DI TANA TORAJA - Guruh Ryan Aulia (AL-Fikr, 2022)
This article discusses inter-religious tolerance in the lovely December celebration in Tana Toraja. The implementation of this lovely december celebration has several activities, namely; Tedong carnival festival, coffee festival, qasidah festival, culinary festival, tandem paragliding festival, festival of musical drama or ballet, creative economy festival, choir festival, ring road festival Christmas adventure Toraja, ecumenical Christmas celebration, and fireworks festival. Lovely December celebrations have benefits in strengthening brotherly relations in the community. The implementation of these activities is a clear example of the collaboration between religious communities in carrying out these activities and shows an attitude of tolerance between religious communities in Tana Toraja. The elements in realizing tolerance among religious people are; helping each other in carrying out major activities in Toraja, culture being upheld, the government acting actively in increasing tolerance between religious communities, the desire to advance the city of Toraja